SECURITY MANAGEMENT THROUGH THE (NEXT GENERATION) INCIDENT COMMAND SYSTEM MODEL (Security Dialogues, 2024)
The purpose of this paper is to emphasize the importance of application of theappropriate model for security management in contemporary security emergencies. Giventhe complex nature of security situations and the involvement of multiple security actors i.e.institutions in their management, it is essential to deliver an effective outcome and minimizeconsequences and further escalation.In the direction of descriptive elaboration, the models of the incident command systemand the incident command system of the next generation, which is the officially adoptedcrisis management mechanism in the Republic of North Macedonia, are briefly definedand presented. With their organizational hierarchy characteristicsfor human and materialresources designation, they counterpoise a common platform for real-time data sharing andsituational awareness.North Macedonia has adapted the NICS system which is used to coordinate the nationalall-hazards response within the context of civil-military cooperation in various securitycircumstances. The NICS is developed on the Incident Command System developed by theFederal Emergency Management Agency as a standardized approach to multifaceted incidentsfor a coordinated response among different jurisdictions and entities.The initial hypothesis in this paper refers to the premise that in a contemporary environment,the implementation of the optimal security management model should include the dimensionof communication in the form of information and data sharing, coordination of the executionof the decisions made, and a standardized approach to action. The independent variablein addition to the hypothesis is that the application of an appropriate management modelaims to create a flexible response with unified action from multiple relevant institutionsfrom different domains of social activities and should standardize and coordinate the effortsundertaken. The methodology applied for this research includes qualitative and quantitative data analysisfrom relevant primary and secondary sources extracted from field simulation and empiricalexamples, deductive argumentation, comparison method, retrospective review and forecastingconclusions.
Keywords: security, management, command, coordination, model, ICS, NICS, RNM